1978
DOI: 10.1254/jjp.28.391
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Evaluating Bronchomotor and Bronchosecretory Activities: Effects of Prostaglandins and Antigen

Abstract: Abstract-We devised a new

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…o-Adrenoceptor agonists constrict the bronchial (Bruner & Schmidt, 1947;Lung et al, 1976) and tracheal vasculature (this paper), and also decrease tracheal mucosal thickness (Laitinen et al, 1987b). Isoprenaline dilates the bronchial vessels (Lung et al, 1976;Yamatake & Yanaura, 1978) and salbutamol decreases tracheal vascular resistance (this paper). Salbutamol also decreases the permeability of bronchial venules (Persson et al, 1982).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…o-Adrenoceptor agonists constrict the bronchial (Bruner & Schmidt, 1947;Lung et al, 1976) and tracheal vasculature (this paper), and also decrease tracheal mucosal thickness (Laitinen et al, 1987b). Isoprenaline dilates the bronchial vessels (Lung et al, 1976;Yamatake & Yanaura, 1978) and salbutamol decreases tracheal vascular resistance (this paper). Salbutamol also decreases the permeability of bronchial venules (Persson et al, 1982).…”
Section: Discussionmentioning
confidence: 75%
“…Histamine, methacholine and isoprenaline increase bronchial blood flow in sheep when administered directly into the bronchial artery; adrenaline injected similarly reduces bronchial blood flow, and nicotine has a variable effect (Parsons et al, 1985). Histamine (Bruner & Schmidt, 1947;Yamatake & Yanaura, 1978), methacholine (Lakshminarayanan et al, 1985), isoprenaline (Yamatake & Yanaura, 1978) and prostaglandins E2 (Yamatake & Yanaura, 1978) 'Author for correspondence. 2Present address: Research Institute for Military Medicine,Central Military Hospital Tilkka,Mannerheimintie 164,00280 Helsinki 28,Finland. and F2, (Lakshminarayanan et al, 1985) increase bronchial blood flow in dogs, although one report (Yamatake & Yanaura, 1978) describes a vasoconstriction with prostaglandin F2.. Aerosolised histamine increases both bronchial blood flow and airflow resistance, and it is suggested that the action of histamine on bronchial arterioles is mediated by H2-receptors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, at first, we confirmed that the peripheral antitussive effects of local anesthetics can be evaluated by using this preparation, and secondly, investigated peripheral effects of morphine and codeine on the cough reflex. Effects of morphine and codeine on the bronchoconstriction induced by vagal stimulation were also investigated using the method for evaluating airway responses (10).…”
mentioning
confidence: 99%
“…We developed the stopper method in which airway secretory activity can be evaluated by measuring the output of RTF accumulating in the trachea, under conditions of normal ventilation (4,5). This method, however, cannot detect slight changes in the output or allow for an accurate determination of the time course of secretory conditions.…”
Section: Abstract-wementioning
confidence: 99%